Optimalisasi kinerja keuangan: Peran penting manajemen risiko pada perbankan syariah - Mawada, Alifia Aulia (Maliki Interdisciplinary Journal, 2024)
Risk management plays an important role in the sustainability of the company, including in the context of Islamic banking. The purpose of this study is to assess how risk management contributes to the influence of Islamic banking financial performance. Islamic banking risk management includes the identification, measurement, monitoring, and control of various risks arising from the bank’s activities, including credit, reputation, operational, market, legal, strategic, yield, compliance, liquidity, and investment risks. The implementation of risk management is regulated by law and supervised by the Sharia Supervisory Board. The results indicate that the implementation of effective risk management has a good impact on the financial performance of Islamic banking. Islamic banks will benefit from effective risk management by reducing unfavorable risks and increasing firm value.